1989
DOI: 10.1152/ajpregu.1989.257.4.r726
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of calcitonin gene-related peptide in conscious dogs

Abstract: To elucidate the cardiovascular effects of alpha-human calcitonin gene-related peptide (CGRP), we infused CGRP intravenously at increasing rates of 3, 10, and 30 pmol.kg-1.min-1 during successive 15-min intervals into intact dogs, cardiac-denervated (CD) dogs, and cardiac-denervated dogs pretreated with beta-blockers. In intact dogs, the initial infusion rate of CGRP at 3 pmol.kg-1.min-1 did not produce significant hemodynamic changes, but the two higher infusion rates produced dose-dependent decreases in tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1990
1990
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…This is in contrast to the observed tachycardia during pentobarbital anesthesia in the present study as well as in those reported previously [10,11,16,17]. The increases in HR elicited by CGRP during pentobarbital anesthesia may be the results of two major mechanisms: one is the direct positive chronotropic action of CGRP on the heart [18], and the other is a reflex-mediated action on sympathetic tone in response to hypotension [10,11,19].…”
Section: Discussioncontrasting
confidence: 71%
“…This is in contrast to the observed tachycardia during pentobarbital anesthesia in the present study as well as in those reported previously [10,11,16,17]. The increases in HR elicited by CGRP during pentobarbital anesthesia may be the results of two major mechanisms: one is the direct positive chronotropic action of CGRP on the heart [18], and the other is a reflex-mediated action on sympathetic tone in response to hypotension [10,11,19].…”
Section: Discussioncontrasting
confidence: 71%
“…administration of drugs a catheter was placed in a jugular vein through which saline (0.9% NaCl, wt/wt) was continuously infused at a rate of 1.5mlh-' to avoid dehydration. In some experiments the drugs were administered close arterially to the stomach, in which case the abdominal aorta was cannulated with a catheter in a retrograde direction so that the tip of the catheter lay just above the branching of the coeliac artery (Lippe et al, 1989 (Burton & Gorewit, 1984;Wang et al, 1989 (model T106,Transonic).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies in conscious dogs (Wang et al, 1989) and man (Gennari et al, 1989; indicate that human a-calcitonin gene-related peptide (human a-CGRP) can increase cardiac output. However, results of experiments in rats are less clearcut, possibly because of limitations with the methodology used.…”
Section: Introductionmentioning
confidence: 99%